Analysis of hypertension health services in the working area of the Padangsidimpuan City Health Office - Sitompul, Sahran Azhari; Hardisman, Hardisman; Kasra, Kamal (Institute of Computer Science (IOCS), 2025)
The low achievement of hypertension services in the work area of the Padangsidimpuan City Health Office needs to be analyzed on the level of knowledge and attitude of patients, the availability of facilities and infrastructure, and the support of health workers. System components are also analyzed to find out how input, process and output elements are in hypertension services. The research method combines quantitative and qualitative methods sequentially. A sample of 107 respondents was taken proportionally random sampling in the hypertensive population aged ≥ 15 years. The results of the study revealed that 42.1% of patients had low knowledge, 62.6% of patients had a negative attitude, and 57% of the support of health workers was negative. In the system analysis, (input elements) are known to be inadequate in the availability of human resources and the availability of funds. It was concluded that public attitudes, support of health workers, human resources and inadequate budgets have a relationship with low hypertension service achievement. The author's recommendations include the importance of improving public attitudes through more optimal education. The role of the government must be more decisive on the availability of human resources and consistently provide support for the hypertension program budget.